Case Report: Intraoperative radiotherapy as the new standard of care for breast cancer patients with disabling health conditions or impairments - Omosule, Michael; De Silva-Minor, Shiroma; Coombs, Nathan (Frontiers in Oncology, 2023)
In selected patients, intraoperative radiotherapy (IORT) offers an alternative to standard external beam radiotherapy (EBRT) while providing equivalent breast cancer control outcomes. After IORT, most patients do not require external beam radiotherapy and thus avoid the need to travel to and from a radiotherapy centre in the weeks after surgery. EBRT is associated with an increased risk of non-breast cancer mortality and poorer cosmetic outcomes while increasing patient travel time, emissions associated with travel and time spent in the hospital. Consequently, EBRT is associated with an overall reduction in quality of life compared to IORT. Patients with other on-going health conditions or clinical impairments are likely to be affected by the daily radiotherapy requirement. Should these patients be consulted during their pre-operative assessment as to options to undergo IORT? This paper describes a case of IORT and follow up in a functionally blind patient. Quality of life effects are elucidated and further support the use of IORT in selected breast cancer patients with health conditions or impairments.